PENGARUH SINERGITAS ERGONOMI PARTISIPATORI DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEBOSANAN, KELELAHAN DAN HASIL BELAJAR IPA SMP - Ni Putu Apriantini; Desak Made Citrawathi; Ida Bagus Putu Aryana (Postgraduate, University of Mataram, 2025)
The inquiry learning model certainly has shortcomings in its implementation, one of which is controlling student activities and success. This model is difficult to observe students who are not participating in groups doing experimental activities. This causes uneven delivery of material for students individually. Therefore, it is necessary for this learning model to be synergized with a participatory approach. One approach that can be used is the Participatory Ergonomics Approach. This study aims to determine whether there is a difference in the effect of the synergy of participatory ergonomics with guided inquiry learning models with conventional learning on junior high school students' eye fatigue, to determine whether there is a difference in the effect of the synergy of participatory ergonomics with guided inquiry learning models with conventional learning on junior high school students' boredom in learning, to determine whether there is a difference in the effect of the synergy of participatory ergonomics with guided inquiry learning models with conventional learning on junior high school students' science learning outcomes, and to determine whether there is a difference in boredom, fatigue and science learning outcomes of students who are taught using the participatory ergonomics approach with guided inquiry models with conventional learning for junior high school students. This type of research is a quasi-experimental researchs. This study uses a quantitative approach. The design of this study uses the Nonequivalent Pretest Posttest Control Group Design. The data in this study are in the form of learning interest questionnaire scores and learning outcome test scores which are analyzed using the MANOVA test. The results of this study indicate that: a significant value of 0.000 (p <0.05) was obtained, a significant value of 0.000 (p <0.05) was obtained, a significant value of 0.000 (p <0.05) was obtained.